2014
DOI: 10.1111/1748-8583.12054
|View full text |Cite
|
Sign up to set email alerts
|

HRM systems between control and commitment: occurrence, characteristics and effects on HRM outcomes and firm performance

Abstract: In the literature, it is often assumed that traditional, control-oriented HRM systems are increasingly being replaced by commitment-based HRM systems because the latter generally result in higher firm performance. However, an HRM system's effectiveness may depend on an organisation's external and internal context, and neither control nor commitment HR systems are without disadvantages. Thus, the empirical validity of this claim is not clear ex ante. This paper analyses the empirical diffusion and determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 47 publications
7
102
0
2
Order By: Relevance
“…The most important contribution is that we explicitly define well-being practices as an essential element of HR practices that deserves separate attention. This takes our perspective on high commitment HR one step further than, for example, the study of Hauff et al [53] who also confirmed the potential beneficial influence of high commitment HRM operationalized in a more traditional way. This HR well-being bundle has clearly been neglected in previous research for its role of in collective turnover, as is exemplified by its not being included in Heavey et al's recent meta-analysis [21].…”
Section: Discussionsupporting
confidence: 50%
“…The most important contribution is that we explicitly define well-being practices as an essential element of HR practices that deserves separate attention. This takes our perspective on high commitment HR one step further than, for example, the study of Hauff et al [53] who also confirmed the potential beneficial influence of high commitment HRM operationalized in a more traditional way. This HR well-being bundle has clearly been neglected in previous research for its role of in collective turnover, as is exemplified by its not being included in Heavey et al's recent meta-analysis [21].…”
Section: Discussionsupporting
confidence: 50%
“…By conceptualizing HRM as a continuum from low to high commitment rather than as distinct HRM approaches, past research may have been unable to show how the leader compensates for transactional HRM approaches. Thus, our findings add to the existing research by studying multiple distinct HRM approaches instead of a continuum from low to high commitment (Guest et al, 2012;Hauff et al, 2014). This approach has allowed us to further unravel the joint role of HRM and the leader.…”
Section: Theoretical Implicationsmentioning
confidence: 53%
“…Studying the employment relationship would be fruitful because it offers a conceptualization of multiple, distinct HRM approaches (Tsui & Wu, 2005). This allows a more nuanced study of HRM than a control-commitment continuum (Guest, Paauwe, & Wright, 2012;Hauff, Alewell, & Hansen, 2014). Specifically, by introducing the employment relationship as a moderator, it is our aim to further the insights on the joint role of HRM and the leader (Kuvaas & Dysvik, 2010;Purcell & Hutchinson, 2007).…”
Section: Insert Figure 1 About Here ------------------------------mentioning
confidence: 99%
“…Одна из базовых классификаций стратегий УЧР выделяет стратегию, ориентированную на контроль, и стратегию, ориентированную на приверженность [Arthur, 1994;Hauff, Alewell, Hansen, 2014]. Эти стратегии опре-деляют основные компоненты системы УЧР (какие практики УЧР обеспечивают нужный результат) и формируют целевое представление о человеческом капита-ле компании (какими должны быть сотрудники).…”
Section: взаимодействие стратегий управления знаниями и стратегий упрunclassified
“…В реальности существует ряд про-межуточных типов стратегий: в одних доминирует контроль, в других -привер-женность, в третьих -сочетаются характеристики обеих стратегий (см., напр. : [Arthur, 1994;Hauff, Alewell, Hansen, 2014] Сильно выражено С о с т а в л е н о п о: [Arthur, 1992;1994;Bae, Lawler, 2000;Lepak, Snell, 2002;Toh, Morgeson, Campion, 2008;Wang, Shyu, 2008;Chow, Liu, 2009;Chow, Teo, Chew, 2013;Hauff, Alewell, Hansen, 2014;Rompho, 2017].…”
Section: взаимодействие стратегий управления знаниями и стратегий упрunclassified